2016
DOI: 10.1002/dmrr.2865
|View full text |Cite
|
Sign up to set email alerts
|

T‐lymphocyte and glycemic status after vitamin D treatment in type 1 diabetes: A randomized controlled trial with sequential crossover

Abstract: A daily vitamin D dose of 4000 IU for 3 months was well tolerated and enhanced Tregs in males. Glucometabolic control improved in all. Subsequent larger trials need to address ß-cell function and genotyping for individualized vitamin D doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 38 publications
1
31
0
1
Order By: Relevance
“…The potential to modify the development of T1D was reported in a case-control study and a birth cohort follow-up study from Finland: it strongly indicated that vitamin D supplementation in infancy decreases the risk of T1D [113,114]. The therapeutic benefit of vitamin D onT1D was tested in some clinical trials [2] but only few studies examined the effect of the vitamin D SNPs in the context of vitamin D supplementation for T1D [115,116,117]. We recently performed a randomized, double-blind, placebo-controlled trial with cross-over design in which thirty-nine patients with T1D received 4000 IU/day cholecalciferol for three months followed by placebo or in reverse sequence.…”
Section: Vitamin D Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential to modify the development of T1D was reported in a case-control study and a birth cohort follow-up study from Finland: it strongly indicated that vitamin D supplementation in infancy decreases the risk of T1D [113,114]. The therapeutic benefit of vitamin D onT1D was tested in some clinical trials [2] but only few studies examined the effect of the vitamin D SNPs in the context of vitamin D supplementation for T1D [115,116,117]. We recently performed a randomized, double-blind, placebo-controlled trial with cross-over design in which thirty-nine patients with T1D received 4000 IU/day cholecalciferol for three months followed by placebo or in reverse sequence.…”
Section: Vitamin D Pathwaysmentioning
confidence: 99%
“…Furthermore, this trial also showed an improvement of glycemic parameters under vitamin D treatment. Patients carrying the genotypes aa, TT and bb (rs7975232 ApaI , rs731236 TaqI and rs1544410 BsmI ) were capable of raising their Treg cell number [115]. A further study tested in vitro the functional role of the VDR rs10735810 ( FokI ) SNP in T-helper (CD3 + CD4 + ) from twenty patients with T1D.…”
Section: Vitamin D Pathwaysmentioning
confidence: 99%
“…Studies from Saudi Arabia, Egypt, Germany and Italy also indicated that vitamin D supplement therapy could improve glycemic control in children and adolescent with T1DM (14,(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…Even 3000 IU/day of cholecalciferol used in the present study could barely sustain 25-(OH) D concentrations in sufficient ranges. Another study also suggests that cholecalciferol doses of 4000 IU/day are well tolerated and associated with enhancement of Tregs in T1D [28].…”
mentioning
confidence: 94%
“…Higher sun-exposure scores resulting in higher 25-(OH)D concentrations may affect the response to oral vitamin D [12]. Finally, the molecular mechanism of immunomodulation by cholecalciferol remains unexplained in our patients because we did not include the T-cell parameters as studied previously [11,13,28].…”
mentioning
confidence: 99%